Estimation of mineral liberation distribution functions to be used in modelling of impact and attrition milling. (1st November 2021) - Altun, Okay; Altun, Deniz
Abstract: The paper aimed to reveal the liberation behaviours to define a methodology for calculating the liberation distribution functions of the minerals. This function can be incorporated into the existing comminution modelling so that the accuracy of the mineral-specific predictions is further improved. Within the scope, grinding tests were performed with complex copper ore, which was subjected to the ball and stirred milling. Following the grinding tests, size intervals were prepared for MLA where the mineral contents and liberation degrees of minerals of interest were determined. The data interpretation included the calculation of liberated galena, sphalerite, chalcopyrite and pyrite minerals' amount to make a comparison between the technologies and the minerals. The study showed that the attrition milling produced more liberated minerals and galena had the highest degree of liberation irrespective of the technology chosen. Afterwards, a methodology similar to express the breakage events (t10 ) was developed to determine the liberation distribution function. This function implies the energy-dependent distribution of the liberated minerals to the subsequent sizes. This was named as L10 and determined for each of the grinding technology and mineral. Initial model fitting of the minerals via perfect mixing model showed that there was a good agreement between the measured and calculated size distributions however further improvements may be considered. As a result, the comminution modelling of both technologies was accomplished.